Craniofacial morphology in Turner syndrome patientstreated with growth hormone - Juloski, Jovana; Scepan, Ivana; Stefanovic, Neda; Pajevic, Tina; Markovic, Evgenija; Glisic, Branislav (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: In addition to well-established physical characteristics, Turner syndrome patients have distinct craniofacial morphology.Since short stature is the most typical characteristic, Turner syndrome patients are commonly treated with growth hormone in orderto increase final height. At the same time, growth hormone treatment was found to influence craniofacial growth and morphologyin various groups of treated patients. Whereas craniofacial characteristics of Turner syndrome patients are well documented,comparatively little is known of craniofacial morphology of those who are treated with growth hormone.Aim: The aim of this study was to investigate craniofacial morphology in Turner syndrome patients treated with growth hormone incomparison to healthy females.Materials and methods: The cephalometric evaluation was conducted on twenty lateral cephalograms of Turner syndrome patients(13.53 ± 4.04 years) treated with growth hormone for at least one year (4.94 ± 1.92 years in average). As a control group, fortylateral cephalograms of healthy female controls, who matched Turner syndrome patients by chronological (11.80 ± 2.37 years) and skeletal age, were used. Eleven angular, seven linear measurements and six dimensional ratios were measured to describe craniofacial morphology.Results: The results obtained for angular measurements, in cephalometric analyses for Turner syndrome patients treated with growth hormone, revealed bimaxillary retrognathism. The linear measurements indicated longer mandibular ramus, anterior cranial baseand both anterior and posterior facial heights. However, ranial base and maxilla were in proportion to the anteriorcranial base, when comparing dimensional ratios. Anterior cranial base, maxilla and mandibular ramus were larger in proportion tomandibular body; as well as posterior facial height was when compared to anterior facial height.Turner syndrome patients treated with growth hormone expressed distinct craniofacial morphology compared to controls. Apart from retrognathic maxilla and mandible, they exhibited over developed mandibular ramus height and elongated facial heights.Conclusions: The results from this study have shown that Turner syndrome patients treated with growth hormone expressed distinct craniofacial morphology compared to controls. These differences include retrognathic maxilla and mandible, over developed mandibular ramus height and elongated facial heights. This specific craniofacial morphology was formed under combined influenceof X chromosome deficiency and growth hormone therapy.